Desain Tata Kelola Rekam Medis Berbasis Elektronik Dalam Sistem Sensus Harian Rawat Jalan - Fadhil Rifky Saefulloh; Muhammad Siraz Ferdiansyah; Falaah Abdussalaam; Irda Sari (JUSIFO : Jurnal Sistem Informasi, 2023)
The medical record activity is supported by the creation of a daily outpatient census as one of the supporting factors. The daily outpatient census is a routine recording activity in each outpatient installation that records the quantity and relevant information about the served patients. Observational approach is used to identify issues arising in the patient recording process. This research focuses on the implementation of an electronic-based system design to record outpatient data using Microsoft Visual Studio 2010 in a hospital in Bandung. The software development process is carried out using the waterfall approach. Interviews and data collection processes are conducted alternately in this study to obtain clear information. The results of this research indicate that the design of an electronic-based outpatient census system has been successfully developed. System maintenance is crucial to ensure smooth operational processes and minimize errors in recording outpatient census data.